2021
DOI: 10.1111/jth.15279
|View full text |Cite
|
Sign up to set email alerts
|

Device‐induced platelet dysfunction in patients after left ventricular assist device implantation

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Heart failure is a risk factor for stroke in patients with atrial fibrillation (39) and therefore one could expect a similar mechanism in our series. Another explanation may be an altered expression of platelet receptors P-selectin, GPIbα and PECAM-1 in context of oxidative stress linked to a high bleeding risk as recently described by Klaeske et al (35). Furthermore, most of our patients were on any anti-platelet medication or anti-coagulated with LMWH or oral anticoagulation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Heart failure is a risk factor for stroke in patients with atrial fibrillation (39) and therefore one could expect a similar mechanism in our series. Another explanation may be an altered expression of platelet receptors P-selectin, GPIbα and PECAM-1 in context of oxidative stress linked to a high bleeding risk as recently described by Klaeske et al (35). Furthermore, most of our patients were on any anti-platelet medication or anti-coagulated with LMWH or oral anticoagulation.…”
Section: Discussionmentioning
confidence: 81%
“…The etiologies of postoperative bleeding are multifactorial and include thrombocytopenia and activation of fibrinolytic systems. In particular, the recognition of postoperative platelet dysfunction as an important risk factor for bleeding (32) has prompted extensive research in the field of LVAD-induced platelet dysfunction in recent years (33)(34)(35). This research discovered the importance of both acquired von Willebrand syndrome (AvWS) (33,34) and platelet receptor alterations (35) after LVAD implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies have shown that this form of treatment leads to changes of the following platelet receptors: GPIbα, P-selectin, and PECAM-1. Furthermore, elevated oxidative stress may lead to the exacerbation of nonsurgical bleeding in these patients [23].…”
Section: Bleeding During Lvad Therapymentioning
confidence: 99%
“…Elevated oxidative stress biomarkers, platelet receptor shedding of glycoprotein (GP) Ibα, GPVI and an activation of GPIIb/IIIa were reported in patients with post-implant bleeding complications [ 6 , 9 , 10 , 11 , 12 , 13 , 14 ]. Therefore, the loss of functional surface receptors results in a defective platelet function and may contribute to an increased bleeding risk in LVAD patients.…”
Section: Introductionmentioning
confidence: 99%